Changes in Business Structure as a Factor Reflecting the Development of the Region - Vladimír Hiadlovský; Ivana Šidová (Barometr Regionalny, 2013)
The improvement and acceleration of the development of regions in the European Union is the key issue of many EU documents. Presently the Strategy Europe 2020 is considered the most important document. According to it, the development of regions contributes to intelligent growth, which is one of the EU priorities. One of the factors which directly reflects the development of a region is the business structure and its changes. The business structure in Slovak regions has changed under the influence of the economic crisis. The aim of this paper is to analyze the changes in the business structure in Slovak regions and to assess whether these changes have contributed to the development of the region. The data used in the analysis were mainly obtained from the Slovak Statistics Office and other relevant sources.